Effect of Thematic-Based Instruction on Fourth Graders’ Understanding of Science Concepts at SDN Sikumana 2 : Pengaruh Pengajaran Berbasis Tematik terhadap Pemahaman Konsep IPA Siswa Kelas IV di SDN Sikumana 2 - Angeline Arnoldus; Heryon Bernard Mbuik; Susana Juniken Sau; Loisa Bureni; Wasti Reghina Boys (JURNAL PENDIDIKAN IPS, 2025)
The aim of this study is to analyze the ways in which thematic learning influences students so that they understand science concepts in fourth grade. It is the low level of students’ conceptual understanding within science that drives at this research, and rote memorization still dominates in fact. A quasi-experimental method uses a quantitative approach within the study. The research design is a pretest-posttest control group design. The experimental group did receive thematic learning treatment at that time. The control group did receive conventional instruction instead of something else. In the study were thirty fourth-grade students divided equally into two groups. The researchers mainly used a test for science concept understanding. That test collected data. For analyzing data, t-tests were involved, along with normality tests and homogeneity tests. Thematic learning students showed a key improvement versus the control group's scores after the tests. Thematic learning connects academic content to students’ real-life experiences. It shows better understanding about science, especially ideas on energy change. Responses from students regarding the thematic learning model were positive. It suggests improved academic outcomes along with a more meaningful and enjoyable classroom environment. Therefore, thematic learning is an effective approach indeed. Elementary science education can get better.